2015
DOI: 10.1002/asia.201500732
|View full text |Cite
|
Sign up to set email alerts
|

Easy Access to Supramolecular Gels of the Nonsteroidal Anti‐inflammatory Drug Diflunisal: Synthesis, Characterization, and Plausible Biomedical Applications

Abstract: By exploiting salt formation, a new series of primary ammonium monocarboxylate salts of a nonsteroidal anti-inflammatory drug, namely, diflunisal, was synthesized. The majority of the salts thus synthesized turned out to be good gelators of various solvents, including the solvents (e.g., methyl salicylate and pure water) typically used for topical gel formulation. Single-crystal X-ray diffraction studies of a few gelator and nongelator salts in the series revealed details of the hydrogen-bonding networks prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…The designed molecular platform can easily incorporate various anti-inflammatory drugs, as demonstrated in our recent works. 12a Moreover, we have incorporated olsalazine into a biocompatible peptide motif 12c that allows mesalazine to be released from the hydrogel upon reduction by the azoreductase secreted by colonic microflora. 15a Moreover, we aim to engineer the hydrogels to pass through the stomach, to reach the target organ, colon, and to adhere onto the disrupted mucosal surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The designed molecular platform can easily incorporate various anti-inflammatory drugs, as demonstrated in our recent works. 12a Moreover, we have incorporated olsalazine into a biocompatible peptide motif 12c that allows mesalazine to be released from the hydrogel upon reduction by the azoreductase secreted by colonic microflora. 15a Moreover, we aim to engineer the hydrogels to pass through the stomach, to reach the target organ, colon, and to adhere onto the disrupted mucosal surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…As the first step towards to that challenging goal, we explore the structural requirements of the molecules that self-assemble in water and bear glycogens and NSAIDs. Based on the previous studies of hydrogelators containing glycogens 11 and NSAID, 12 we covalently link peptides (e.g., nap-phe-phe 13 ), saccharides (e.g., glucosamine 14 ) and an anti-inflammatory drug (i.e., olsalazine 15 ) to generate a new glycoconjugate. We show that the obtained molecules, as multifunctional glycoconjugates, self-assemble to form hydrogels composed of 3D networks of nanofibers under an acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Following similar strategy, Dastidar et al. further developed topical gels from a series of PAM salts of a well‐known NSAID namely diflunisal . In order to study the robustness of PAM synthon and its implication on gelation, some of the primary amines used in this work contained additional hydrogen bonding functionality; majority of the salts ( G64 – G67 ) turned out to be gelators of various solvents including methyl salicylate and pure water.…”
Section: Designing Lmwgsmentioning
confidence: 99%
“…[56] Among these, the primary ammonium monocarboxylate (PAM) synthoni sp articularly important (Scheme 1). [72][73][74] The anti-inflammatory activity of an onsteroidal anti-inflammatoryd rug (NSAID) is known to follow the cyclooxygenase( COX) pathway by acting as an inhibitor of COX enzymes, thereby reducing the intracellularc oncentration of prostaglandin E 2 (PGE 2 ), the consequenceo fw hich is ar eduction of inflammation of cells. [58,59] Recently, we launched an initiativet od evelop drug-delivery systems that would act in as elf-delivery manner.…”
Section: Introductionmentioning
confidence: 99%
“…[62][63][64][65][66][67][68][69][70][71] We, on the other hand, demonstrated that the supramolecular synthon approach, following the organic salt route, was useful in developing self-delivery systems. [72][73][74] The anti-inflammatory activity of an onsteroidal anti-inflammatoryd rug (NSAID) is known to follow the cyclooxygenase( COX) pathway by acting as an inhibitor of COX enzymes, thereby reducing the intracellularc oncentration of prostaglandin E 2 (PGE 2 ), the consequenceo fw hich is ar eduction of inflammation of cells. [75] However,o rally administrated NSAIDs have severals idee ffects, such as gastrointestinal bleeding [76] and worsening of asthma, [77] whichc an be easily avoided if the drug molecule can be converted into at opical gel that is then conveniently applied to treat inflammationinaself-delivery fashion.…”
Section: Introductionmentioning
confidence: 99%